LINGKUNGAN DAN PERILAKU PENDUDUK SEBAGAI FAKTOR RISIKO KEJADIAN FILARIASIS Brugia malayi DI WILAYAH KERJA PUSKESMAS SUKAJADI KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN PROVINSI SUMATERA SELATAN - , Witi Karwiti ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Filariasis disease generally known as elephantiasis is a chronic infectious disease caused by filaria worms that attack lymph gland or duct. Level of filariasis endemicity in Indonesia based on the result of finger blood survey in 1999 belonged to high at Microfilaria (Mf) rate 3.1% particularly at Sumatra and Kalimantan regions. Meanwhile at District of Banyuasin in 1983-2000 Mf Rate was 2.02%. Chronic filariasis cases at District of Banyuasin in 2009 were as many as 133 cases, there was increase to 138 in 2010. Objective: To identify environment condition and community behavior as risk factors of Brugia malayi filariasis transmision at working area of Sukajadi Health Center, Talang Kelapa Subdistrict, Banyuasin Regency, Sumatera Selatan Province. Method: The study was analytic observational with case control retrospective study design. Samples consisted of 23 cases and 23 control purposively taken from patients positively diagnosed as having microfilaria form 2006 to 2010. The independent variables were 1) environmental physical condition (housing and ventilation physical condition)